Positive student law obedience in the digital age in the automation era at Krisnadwipayana University - Gunawan Widjaja (ABDIMAS DEWANTARA, 2022)
The rapid development of technology allows the parties to use the technology's benefits. This study aims to obtain in-depth information about increasing legal compliance among students by optimizing the use of digital applications in the automation era at Krisnadwipayana University. In collecting the data, this study conducted a series of interviews with academics and other academic activities to hear their perspectives regarding the role of universities using digital applications in improving legal compliance for their students. We examine the results of these interviews under a phenomenological approach that involves coding systems of evaluation and interpretation data, concluding that they have answered the core problem of this study. After analyzing the data and discussing the results, we can conclude that increasing awareness and obedience to favorable laws among students at Krisnadwipayana University by utilizing digital applications are very innovative and creative. This result is relevant to the demands of the all-digital era, where the benefits of digital applications still include all learning activities, especially the dissemination of compliance and legal compliance among universities. Hopefully, these findings will become meaningful inputs for similar studies in the future.